HUBUNGAN ANTARA KECERDASAN EMOSI DAN PENYESUAIAN SOSIAL PADA MAHASISWA RANTAU TAHUN PERTAMA - Helfi Yuliyanti, Marietha; Santosa Sudagijono, Jaka; Anwar Dani, Robik (Widya Warta, 2021)
This research aimed to determine the relationship between emotional intelligence and social adjustment in the first batch of overseas students in Madiun City. The research hypothesis was the relationship between emotional intelligence and social adjustment in the first batch of overseas students in Madiun City. The number of subjects in this study was 50 people taken based on total sampling and purposive sampling techniques. Data collection in this study used the emotional intelligence scale and social adjustment scale. Validity testing with a limit of 0.25 found as many as 47 valid items on the emotional intelligence scale and 58 valid items on the social adjustment scale. Reliability testing with Alpha Chronbach values 0.07. The reliability on the emotional intelligence scale was 0.902, and on the social adjustment scale was 0.936. Hypothesis testing in this study used product-moment techniques from Karl Pearson, obtained significance of 0,000 (p <0.05) and rt was greater than ro (rt=0,517 > ro(Î±=0,05)=0,273). In conclusion, there was a positive and significant relationship between social adjustment and emotional intelligence in the first batch of overseas students in Madiun City.